Vetting for Virtue: Democracy's Challenge in Excluding Criminals from Office - Sigurd S. Arntzen; Jon H. Fiva; Rune J. Sørensen (CESifo GmbH, 2024)
This paper assesses the effectiveness of democratic systems in preventing individuals with criminal backgrounds from holding political office. Unlike many countries, Norway has no legal restrictions against felons running for office. We analyze local election candidates from 2003 to 2019, paired with administrative records of criminal offenses. We demonstrate that individuals with criminal records are systematically penalized at every stage of their political careers. Candidates are less likely to have criminal records than the general population, with elected officials less likely to have criminal backgrounds than their unelected peers, and mayors being the most lawful. Through a series of counterfactual exercises, we demonstrate that the most significant reduction in criminal involvement occurs at the nomination stage, especially within established local party organizations.
Keywords: D72; D73; J24; 330; political selection; criminal backgrounds; voter behaviour; political parties